Business process management workshops : BPM 2015, 13th International Workshops, Innsbruck, Austria, August 31 - September 3, 2015. Revised papers /: BPM 2015, 13th International Workshops, Innsbruck, Austria, August 31 - September 3, 2015. Revised papers. (2016) - Unknown
No abstract available